SUSTAINABILITY MARKETING MIX ON PURCHASE DECISION THROUGH CONSUMER’S GREEN ATTITUDE AS THE MODERATING VARIABLE - Nindya Saraswati; Aditia Wirayudha (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Today, the importance of sustainability is increasing as environmental issues have become a concern for both businesses and consumers. Companies must swiftly comprehend the idea of sustainability and begin to assess themselves as businesses need to make a profit to survive, but to be sustainable, they need to balance the other two priorities, namely people and the planet. Hence, the idea of sustainable marketing has emerged. It focuses on the need to practice sustainability as well as to meet the needs, without harming future generations, by having green movement as core business goals. This study aims to identify the influence of sustainability marketing mix in purchasing decisions towards green personal care products, The Body Shop, in the Indonesian context and to reveal the role of consumer’s green attitudes as moderating variable. This is a quantitative research. Meanwhile, the data analysis technique consists of testing the validity and reliability, simple linear regression, hypothesis testing and moderated regression analysis. The findings show that the sustainability marketing mix has a positive and significant effect on purchasing decisions for green products in Indonesia, moderated by consumer’s green attitude.